HIV Entry Revisited - Uchil, Pradeep D. (2009)
HIV has long served as a model for viruses that enter cells by direct fusion at the plasma membrane. Miyauchi et al. (2009) now provide compelling evidence that HIV enters cells primarily by endocytosis.